Identification of sperm immunoreactive antigens for immunocontraceptive purposes: a review - Domagala, Alina (BioMed Central, 2004)
Antisperm antibodies (ASA) may be a reason of infertility in some individuals. They may affect pre- as well as post-fertilization stages of the reproductive process. There is ongoing progress in the identification of sperm antigens related to fertilization. The employed methods for this purpose include recombinant DNA technology and the most advanced proteomic analysis. This paper enlists the different approaches undertaken in order to identify and characterize the immunoreactive sperm antigens. We have mainly focused on those, which have been already studied in regard of their immunocontraceptive potential, although it has been impossible to include all published data concerning the topic in a single article. Few novel sperm auto- and isoantigens, discovered recently, have also been reviewed even if their role in fertilization has not been yet established.